Kajian tentang Kompetensi Peradilan Mahkamah Konstitusi Terkait dengan Penetapan Pasangan Calon Kepala Daerah - Muhammad Ridhwan (JURNAL RECHTENS, 2014)
Amendments to the 1945 Constitution , has resulted in a fundamental change that is putting people's sovereignty in the hands of the people who carried out according to the Constitution . Means that the sovereignty of the people remain in the hands of them, as a real form of sovereignty vested in the people in the implementation of the state . Election systems can be realized through the structuring of the system and the quality of the election. Constitution of 1945 outlines the principles of a free and fair election in held as set forth in the Law. In a change that is governed by the provisions of Article 1 act (2) that are intended to optimize and understand sovereignty that followed in Indonesia . Furthermore, elections that are contained in Article 1 act (2) of the Constitution of 1945, sovereignty in people held upon the Law through democratic election to get representatives with integrity, capability, and moral accountability as public officials. Article 24C asserts that "The Constitutional Court has the authority to hear at the first and the last with a final decision to test the Law towards Constitution of 1945, to decide disputes in state institutions with the authority given by the Constitution of 1945, dissolution of political parties, and decide disputes about the results of elections. The Constitutional Court shall make a decision on the opinion of the House of Representatives regarding the alleged violations by the President /Vice- President according to the Constitution.